Voluntarism as Social Capital of Community Radio Management: a Case Study in Jarik III Cirebon - Lilis Ch, Dede; Rochim, Mochamad; Yuliati, Nova (KOMUNITAS: INTERNATIONAL JOURNAL OF INDONESIAN SOCIETY AND CULTURE, 2016)
Community radio networking (Jarik) III Cirebon is the affiliation of community radio in Cirebon, Kuningan, Majalengka and Indramayu regencies. Jarik III consists of 11 community radios. Besides broadcasting, Jarik is active in social action. They have been defending people especially in human trafficking and domestic violence cases. Based on voluntarism perspective, this article elaborates how those radios mitigate the societyâs issue. This article was based on research through qualitative method using case study. The data was obtained through interview, observation, and documentation with three community radio FM administrators, namely Baina FM, Bhuana FM, and Caraka FM. The finding of the study shows that the background of the establishment, purpose and community radio operations are based on socio-demographic condition of their own community; society-based service becomes an administrator community radioâs spirit; and voluntarism underlying administrator performance of community radio helps overcoming peopleâs problem.